A 60-years old field experiment demonstrates the benefit of leys in the crop rotation. (2nd January 2019) - Zhou, Zhenjiang; Palmborg, Cecilia; Ericson, Lars; Dryler, Kent; Lindgren, Kim; Bergkvist, Göran; Parsons, David
ABSTRACT: In the 1950s, a long-term experiment was initiated at three locations in Northern Sweden. The treatments included four cropping systems, which differed in the number of years with leys or annual crops in the crop rotation. To create awareness of the experiment as a research resource for further scientific studies, we summarise the history (experimental design, materials and methods, main measurements) and scientific findings of the experiment, as well as reflect on its usefulness and opportunities for further studies. So far, scientific focus has been on the effects of cropping systems on soil characteristics. The main findings indicate that soil porosity and hydraulic conductivity were greater in cropping systems with a large proportion of ley, soil bulk density showed the opposite trend. In terms of chemical properties, cropping systems incorporating more ley also have greater soil organic carbon content than annual crops systems, and both soil carbon and N storage decrease over time in cropping systems with only annual crops. The effects of cropping system on crop yields and quality are areas for further investigation.